HUBUNGAN PENGETAHUAN SEKSUAL PRANIKAH DENGAN PERILAKU SEKSUAL REMAJA DI SMK X NEGARA - Adi Pratama, Gede Surya; Suindrayasa, I Made; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing; Vol 9 No 3 (2021): Juni 2021, 2021)
Premarital sexual knowledge is informatian about sexual before marriage. Inadequate adolescents understanding about premarital sex may lead to inappropriate sexual behavior. This study aims to determine the corelation between premarital sexual knowledge and adolescent sexual behvior in SMK Negeri X Negara. This research is a descriptive correlative study with cross sectional aproach. The sample consisted of 100 students selected by total sampling. Data collected with a questionnaire to determin the score of premarital sexual knowledge and sexual behavior. Based on the Spearman Correlation test obtained p value = 0.005 (? ? 0.05) and r = -0.277. It can be concluded that there is a corelation between premarital sexual knowledge and adolescent sexual behavior with the direction of a negative relationship and the strength of the two variable is statistically weak. The better premarital sexual knowledge, the lower the risk of adolescents to inappropriate sexual behavior. But there are still other factors that influence sexual behavior besides knowledge. It is expected that students seek information about sexuality correctly and from trusted sources to avoid inappropriate sexual behavior.